A new leafhopper genus of Empoascini (Hemiptera, Cicadellidae, Typhlocybinae) from China - Yu, Xiaofei (Zookeys, 2020)
Abstract. A new leafhopper genus, Fanjingagen. nov., with type species F. digitata Yu & Yang, sp. nov., is described from the Guizhou Province of Southwest China. Habitus photos and illustrations of male genitalia of the new species are provided.